2007
DOI: 10.3989/asclepio.2007.v59.i2.231
|View full text |Cite
|
Sign up to set email alerts
|

El Laboratorio Foster de la Residencia de Señoritas. Las relaciones de la JAE con el International Institute for Girls in Spain, y la formación de las jóvenes científicas españolas

Abstract: In the first third of the twentieth century, relations among American and Spanish university women began; particularly the relationship between the JAE and the International Institute for Girls in Spain had a positive influence in the education of women scientists in Spain. An interchange of students and teachers came out from this relationship, and Spanish women received scholarships to stay in American universities. The history of the Foster Laboratory and some biographical notes of her founder are included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…(Huguet, 2012) We can frame our protagonist in this Anglo-Saxon profile, since as we have demonstrated in the text, she was educated at the International Institute for Girls, a pioneering Protestant institution in higher education for Spanish women. (Magallón, 2007). The study of the educational system used and relations carried out by the International Institute to develop its work in a society ultra-Catholic as the Spanish of the time (Huguet, 2012), allowed us to carry out our research and achieve the indicated objectives to highlight the educational work carried out by Carolina Marcial Dorado, beginning with her Protestant education.…”
Section: Resultsmentioning
confidence: 99%
“…(Huguet, 2012) We can frame our protagonist in this Anglo-Saxon profile, since as we have demonstrated in the text, she was educated at the International Institute for Girls, a pioneering Protestant institution in higher education for Spanish women. (Magallón, 2007). The study of the educational system used and relations carried out by the International Institute to develop its work in a society ultra-Catholic as the Spanish of the time (Huguet, 2012), allowed us to carry out our research and achieve the indicated objectives to highlight the educational work carried out by Carolina Marcial Dorado, beginning with her Protestant education.…”
Section: Resultsmentioning
confidence: 99%
“…).Los laboratorios Foster eran los laboratorios situados en la Residencia de Señoritas(Magallón, 2007) fundados por Mary Louise Foster. Rosa Herrera era la directora y María Luz Navarro su ayudante.…”
unclassified
“…In this framework, we wonder how it has been in Spain. In this country, along the last two decades have been rescued the context and the scientific profile of the Spanish pioneering women in sciences, as well as have been made biographical, statistical and prosopographical studies of these pioneers (Barral Morán et al, 1999;Santesmases, 2000;Alcalá et al, 2005;Delgado Echeverría, 2007;Magallón Portolés, 2004, 2007a, 2007b, and Miqueo Miqueo, Germán Bes, Fernández Turrado & Barral Morán, 2011. How is it nowadays?…”
mentioning
confidence: 99%